2000-ЖЫЛЛАРДАҒЫ ҚАРАҚАЛПАҚ РОМАНЫ: ТАРИЙХЫЙ ДӘРЕК ҲӘМ ЖАЗЫЎШЫНЫҢ КѲРКЕМ ҚЫЯЛЫ - Нуржанов, П. (SCIENCE and SOCIETY, 2022)
The article analyzes the problem of the Karakalpak historical novel of the 2000s and the uniqueness of the creation of the hero's image on the example of K. Karimov's work "Darvish".
Keywords: historical fact; writer's artistic fantasy; historical novel; image of a historical hero; monologue; dialogue; national flavor; artistic psychologism; plot; composition